2015
DOI: 10.1186/s40064-015-1330-y
|View full text |Cite
|
Sign up to set email alerts
|

Increase in participation but decrease in performance in age group mountain marathoners in the ‘Jungfrau Marathon’: a Swiss phenomenon?

Abstract: Participation and performance trends for age group marathoners have been investigated for large city marathons such as the ‘New York City Marathon’ but not for mountain marathons. This study investigated participation and trends in performance and sex difference in the mountain marathon ‘Jungfrau Marathon’ held in Switzerland from 2000 to 2014 using single and mixed effects regression analyses. Results were compared to a city marathon (Lausanne Marathon) also held in Switzerland during the same period. Sex dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
1
12
1
Order By: Relevance
“…Differences of course times between city marathons and Napfmarathon were analyzed with two-sided paired t-tests. The analyzed polynomial Interpolation 2 Degree for the matched sample yielding to an u-shaped age course time relationship with optimal age of 34 years in Napfmarathon and 35 years in city marathons (Figure 4), whereby these findings are supported by others [24]. If all course times are taken, local minimum for men is around 34 years nearly equivalent for both competitions forms ( Figure 5).…”
Section: Statistical Proceduressupporting
confidence: 71%
See 1 more Smart Citation
“…Differences of course times between city marathons and Napfmarathon were analyzed with two-sided paired t-tests. The analyzed polynomial Interpolation 2 Degree for the matched sample yielding to an u-shaped age course time relationship with optimal age of 34 years in Napfmarathon and 35 years in city marathons (Figure 4), whereby these findings are supported by others [24]. If all course times are taken, local minimum for men is around 34 years nearly equivalent for both competitions forms ( Figure 5).…”
Section: Statistical Proceduressupporting
confidence: 71%
“…If all course times are taken, local minimum for men is around 34 years nearly equivalent for both competitions forms ( Figure 5). In woman with 28.7 years a lower value results a pattern also found for Jungfraumarathon where reasons were attributed towards differences in lean mass [22,[24][25][26][27] (Figure 6). Trying to compare results from statistical regressions, with β=1.7 for Napfmarathon versus β=2.1 for city marathon a smaller increase in course times results with increasing age (Figure 3) Furthermore, R2=0.15 for Napfmarathon is smaller than R2=0.19 for city marathons (Figure 3).…”
Section: Statistical Proceduresmentioning
confidence: 80%
“…Generally, men are running faster than women when competing at both world class level 1,2 and at recreational level. 10 The sex difference remained stable in running distances from 100 m to the marathon in the last decades in elite athletes. 13,14 However, this difference is most likely due to the number of selected athletes for an analysis because most running studies investigated generally a limited sample of the best athletes for each age-group.…”
Section: Master Men Were Faster Than Master Womenmentioning
confidence: 99%
“…Furthermore, a study investigating master athletes in the '100 km Lauf Biel' showed a decrease in participation of younger age group runners [28]. In relation to the famous 'Jungfrau Marathon', a mountain marathon with worldwide participation that also hosts the World Championship in mountain marathon running, participation increased in age group runners, but performance was found to be impaired [29]. Obviously, for some races held in Switzerland, important changes took place in both participation and performance with a decrease in participation.…”
Section: Introductionmentioning
confidence: 99%